تأثير الرعاية الابوية على التفوق الدراسي - دراسة ميدانية في المرحلة الابتدائية- - حريزي صليحة; اشراف: بوسكرة عمر (جامعة محمد بوضياف المسيلة, 2025)
تهدف هذه الدراسة إلى الكشف عن العلاقة بين مستوى الرعاية الأبوية التي يتلقاها التلميذ في البيئة المنزلية، ومدى تأثيرها على تحقيق التفوق الدراسي في المرحلة الابتدائية. كما تسعى إلى تحديد أبعاد الرعاية (العاطفية، التعليمية، الصحية، والرقابية) التي تسهم بفعالية في دعم المسار الدراسي للطفل. حيث تبرز أهمية هذه الدراسة في كونها تركز على مرحلة حاسمة في التكوين المعرفي والنفسي للطفل، حيث يعتبر التفوق الدراسي في المرحلة الابتدائية أساسا لبناء شخصية متوازنة ومتعلمة. كما أنها تسلط الضوء على دور الأسرة كعنصر فاعل في دعم المدرسة، مما يسهم في تحسين جودة التعليم والحد من الفشل الدراسي. وقد اعتمدت الدراسة على المنهج الوصفي التحليلي من خلال إجراء دراسة ميدانية شملت عينة من تلاميذ المرحلة الابتدائية وبعض أوليائهم وأساتذتهم، وذلك باستخدام أدوات جمع البيانات مثل الاستبيانات والمقابلات. وتم تحليل المعطيات باستخدام تقنيات إحصائية لقياس العلاقة بين مستوى الرعاية الأبوية والتحصيل الدراسي. وقد توصلت الدراسة إلى أن هناك علاقة طردية قوية بين مستوى الرعاية الأبوية والتفوق الدراسي لدى التلاميذ، حيث تبين أن الأطفال الذين يحظون بدعم عاطفي ومتابعة تعليمية منتظمة من طرف أوليائهم يحققون نتائج دراسية أعلى من أقرانهم الذين يعانون من ضعف في هذا الجانب. كما تبين أن غياب الحوار الأسري والاهتمام الدراسي ينعكس سلبا على الأداء الأكاديمي. كما أوصت الدراسة بضرورة تعزيز وعي الأولياء بأهمية دورهم التربوي في دعم التحصيل الدراسي لأبنائهم، من خلال تنظيم ورشات تربوية بالتعاون مع المؤسسات التعليمية. كما دعت إلى إنشاء برامج شراكة بين المدرسة والأسرة تتيح تواصلا دائما وتفاعلا مثمرا. وأكدت على أهمية توفير بيئة منزلية مستقرة وآمنة عاطفيا لتشجيع الأطفال على النجاح. وعليه فإن نتائج هذه الدراسة تبرز بوضوح أن الرعاية الأبوية ليست مجرد عامل مساعد بل هي دعامة أساسية للتفوق الدراسي في المرحلة الابتدائية؛ مما يحتم تكاثف الجهود بين الأسرة والمدرسة لضمان نمو سليم ومتكامل للطفل على المستوى الأكاديمي والنفسي والاجتماعي. الكلمات المفتاحية: الرعاية، الرعاية الأبوية، التفوق الدراسي، التلميذ، الوسط المدرسي.   Abstract: This studyaims to explore the relationshipbetween the level of parental care received by a pupil in the home environment and its impact on achievingacademic excellence at the primaryschoollevel. It alsoseeks to identify the dimensions of care—emotional, educational, health-related, and supervisory—thateffectively support the child'sacademicpath. The importance of thisstudy lies in its focus on a critical stage in the cognitive and psychologicaldevelopment of the child, as academic excellence during the primary stage isconsideredfundamental to building a balanced and educatedpersonality. The studyalso highlights the role of the family as an active partner in supportingschools, contributing to improvededucationquality and the reduction of academicfailure. The studyadopted a descriptive-analyticalmethodology by conducting a field investigation involving a sample of primaryschoolpupils, some of their parents, and theirteachers. Data collection toolssuch as questionnaires and interviews wereused, and the data wereanalyzedusingstatistical techniques to measure the relationshipbetween parental care and academicachievement. The studyfound a strong positive correlationbetween the level of parental care and students' academic excellence. It showedthatchildrenwhoreceiveemotional support and regulareducational follow-up fromtheir parents tend to achievehigheracademicresultsthantheirpeerswholacksuch care. It alsorevealedthat the absence of family dialogue and educational attention negatively affects academic performance. The studyrecommendedraising parents’ awareness of theireducationalrole in supportingtheirchildren'sacademicsuccessthrough the organization of educational workshops in cooperationwithschools. It alsocalled for the establishment of school-family partnership programs that enable continuous and productive communication. Furthermore, the studyemphasized the importance of providing a stable and emotionallysecure home environment to encourage children to succeed. Therefore, the results of thisstudyclearlyindicatethat parental care is not merely a supportive factor, but a fundamentalpillar for academic excellence in primaryeducation. This necessitates joint efforts between the family and the school to ensure the child’shealthy and holisticdevelopment on academic, psychological, and social levels.